Istanbul, Türkei. Wissenschaftliche Netzwerke. Die Jahre 2014 bis 2018 - Pirson, Felix; Ludwig, Bernhard (e-Forschungsberichte des DAI, 2018)
The research networks of the Istanbul Department of the DAI are intended to strengthen interdisciplinary cooperation inside the department and with colleagues from German, Turkish and international universities and research institutes. They have run continuously for ten years now and are directed primarily, though not exclusively, at junior researchers. The networks explore overarching archaeology and cultural history related themes with diachronic potential – for example, »Power and Hierarchies in the Urban and Rural Environment« and »Nature and Cult in Anatolia« – which are discussed in a variety of formats (seminars, workshops, excursions and autumn schools) focused on different topics and spread out over two to three years. The participants themselves decide on the content of the individual sessions. Each network should result in a publication consisting of a set of contributions and a synthesizing summary.